Child and adolescent mental well-being intervention programme: A systematic review of randomised controlled trials - Lam, Lawrence T.; Lam, Mary K. (Frontiers in Psychiatry, 2023)
Background There has been an increasing awareness and recognition of mental well-being as one of the main outcome measures in national mental health policy and service provision in recent years. Many systemic reviews on intervention programs for mental health or general well-being in young people have been conducted, however, these reviews were not mental well-being specific. Objective This study aims to examine the effectiveness of child and adolescent mental well-being intervention programs and to identify the approach of effective intervention by reviewing the available Randomised Controlled Trials. Methods This systematic review study followed the PRISMA guidelines for systematic reviews ensuring a methodical and structured approach for the literature search and the subsequent review processes. The systematic literature search utilised major medical and health databases. Convidence, an online application for conducting systematic reviews, was used to assemble the titles, abstracts, and full articles retrieved from the initial literature search. To examine the quality of the included trials for determining the strength of the evidence provided, the JBI Critical Appraisal Tool for Randomised Controlled Trial was used. Results There were 34 studies identified after an extensive search of the literature following the PRISMA guidelines. Seven (7) fulfilled all selection criteria and provided information on the effect of an intervention program on mental well-being in adolescence. Data were extracted and analysed systematically with key information summarised. The results suggested that two (2) programs demonstrated significant intervention effects, but with a small effect size. The quality of these trials was also assessed using the JBI Critical Appraisal Tool for Randomised Controlled Trials and identified some methodological issues. Conclusions In conclusion, activity-based and psychoeducation are shown to be potentially effective approaches for future program development. More research on a well-designed program is urgently needed, particularly in developing countries, to provide good evidence in supporting the mental health policy through the enhancement of mental well-being in young people.